2011
DOI: 10.4103/0973-6247.75972
|View full text |Cite
|
Sign up to set email alerts
|

Hexamoll DINCH plasticised PVC containers for the storage of platelets

Abstract: Introduction:Containers for the storage of platelets are made using polyvinyl chloride plasticised with di, (2-ethyl hexyl) phthalate, n-butyryl, tri (n-hexyl) citrate and tri (2-ethyl hexyl) mellitate or using special poly olefins without plasticiser. Of these, the first two have disadvantages such as plasticiser leaching and impairment of platelet function. Polyolefin bags cannot be HF welded or steam sterilized. Mellitate plasticised bags can store platelets well for five days but they are not completely ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Studies that evaluated canine PC in 100% plasma observed a significant reduction of platelet count, it was associated with platelet activation and formation of microaggregates, fragmentation or loss of platelet integrity, and these may be the reasons of reduction of platelet count during the storage period [ 20 , 21 ]. Our results are in agreement with previous studies evaluating human PC in SSP+ and Composol, where no variation in platelet count was observed [ 3 , 15 , 19 ]. Van der Meer (2012) stated difference in this parameter, the authors suggest that the low viscosity of the PAS, makes it necessary to adapt and standardize the centrifugation protocols [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Studies that evaluated canine PC in 100% plasma observed a significant reduction of platelet count, it was associated with platelet activation and formation of microaggregates, fragmentation or loss of platelet integrity, and these may be the reasons of reduction of platelet count during the storage period [ 20 , 21 ]. Our results are in agreement with previous studies evaluating human PC in SSP+ and Composol, where no variation in platelet count was observed [ 3 , 15 , 19 ]. Van der Meer (2012) stated difference in this parameter, the authors suggest that the low viscosity of the PAS, makes it necessary to adapt and standardize the centrifugation protocols [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Swirling is a non-invasive method for assessing platelet viability; it is caused by light diffraction due to the alignment of normal discoid shaped platelets. In this evaluation zero indicates no swirling and 3 indicates great swirling [ 15 ]. Residual leukocyte count was performed using the Nageotte chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Despite what has been reported in the literature for decades, bags containing plasticizers known to disrupt AAG-drug binding continue to be widely used for blood collection with the intended use in both research and in the clinical setting. DEHP is essential in maintaining the shelf life of blood products up to 42 days as it protects the membrane of the red blood cell (133). Transfusion recipients routinely receive blood that has been collected and stored in these bags.…”
Section: Effect Of Plasticizers On Drug-protein Bindingmentioning
confidence: 99%
“…PLT storage containers with polyolefin are also FDA approved and in use, which do not contain phthalates 46 . Also in development is a nonphthalate plastic container, 1,2‐cyclohexane‐dicarboxylic acid, di‐isononylester for PLT storage 47 …”
Section: Alternativesmentioning
confidence: 99%